33 men : inside the miraculous survival and dramatic rescue of the Chilean miners - Franklin, Jonathan, 1964- (New York : G.P. Putnam's Sons, 2011)
This is the account of the 2010 San Jose mine rescue in Chile, after one of the longest human entrapments in history. With his coveted "rescue pass," the author was permitted access far past the police perimeter. It would be seventeen long days before the miners were discovered alive and the world press descended. It would be another fifty-two days before the miners were all successfully rescued. For eight weeks, the author conducted interviews with families, rescue workers, the mine psychologist, drill operators, scientists, and the architects of the rescue operation. He reported from an improvised office on the mountainside that was the nerve center of the rescue operation, in a makeshift container. Far below, families and loved ones lived in a cluster of tents known as Camp Hope. While the men were still underground, the author interviewed them via a crude telephone; he helped send vital supplies to them via the "Paloma" (pigeon). And when the first miners were rescued on October 13, he had the first media contact with the recently freed men in a series of interviews from inside the field hospital. The book reads like a thriller, toggling between the dramatic chaos below ground as the men realized that their escape routes were blocked and that their shelter held only enough rations for ten men to survive seventy-two hours; and the desperate rescue efforts aboveground, the massive campaign from the top level of the Chilean government to enlist and unite brilliant minds from around the world in the San Jose rescue effort. In never before revealed detail, the author tells a story of the improbable survival of the miners, trapped some 2,200 feet underground for sixty-nine days. He also chronicles what had to go right, an impossibly long list, to rescue them all alive. The death-defying rescue demanded endurance, ingenuity, and most of all, unified fronts above and below ground. To be sure, none of this came easily. Based on more than 110 interviews with the miners, their families, and the rescue team, this account combines an eye for detail and dialogue with the remarkable human interest story of these miners struggling to survive in a savage environment.
Buried alive -- A desperate search -- Stuck in hell -- Speed vs. precision -- 17 days of silence -- A bonanza at the bottom of the mine -- Crawling back to life -- The marathon -- TV reality -- Finish line in sight -- The final days -- The final preparations -- The rescue -- First days of freedom.
Keywords: Gold mines and mining -- Accidents -- Chile -- Copiap243}0Region.; Copper mines and mining -- Accidents -- Chile -- Copiap243}0Region.; Mine rescue work -- Chile -- Copiap243}0Region.; Survival after airplane accidents, shipwrecks, etc. -- Chile -- Copiap243}0Region.; Gold miners -- Chile -- Copiap243}0Region -- Biography; Copper miners -- Chile -- Copiap243}0Region -- Biography; Copiap243}0Region (Chile) -- History -- 21st century; Copiap243}0Region (Chile) -- Biography